2017
DOI: 10.3389/fnhum.2017.00391
|View full text |Cite
|
Sign up to set email alerts
|

Tradeoff between User Experience and BCI Classification Accuracy with Frequency Modulated Steady-State Visual Evoked Potentials

Abstract: Steady-state visual evoked potentials (SSVEPs) have been widely employed for the control of brain-computer interfaces (BCIs) because they are very robust, lead to high performance, and allow for a high number of commands. However, such flickering stimuli often also cause user discomfort and fatigue, especially when several light sources are used simultaneously. Different variations of SSVEP driving signals have been proposed to increase user comfort. Here, we investigate the suitability of frequency modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 29 publications
1
32
1
Order By: Relevance
“…We designed visual stimulus patterns at high-frequency range and obtained similar results (>90%) (Tables 1 , 2 ). Our results for single trials analysis are in the range of 73–74% (Tables 4 , 5 ) and are comparable with (Dreyer et al, 2017 ) that reported 33–87%. Our single trial accuracy rate was also comparable with a recent low frequency study (Zhang et al, 2012b ).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We designed visual stimulus patterns at high-frequency range and obtained similar results (>90%) (Tables 1 , 2 ). Our results for single trials analysis are in the range of 73–74% (Tables 4 , 5 ) and are comparable with (Dreyer et al, 2017 ) that reported 33–87%. Our single trial accuracy rate was also comparable with a recent low frequency study (Zhang et al, 2012b ).…”
Section: Discussionsupporting
confidence: 92%
“…In these studies, a high frequency carrier was modulated by another frequency and the SSVEP was evoked at the difference of these two frequencies that covered low frequency range for improving the accuracy rate. This method reduced subjective perceptibility as well as fatigue rate; however, the accuracy rate in these studies was lower than the simple stimulus used in recent studies (Dreyer and Herrmann, 2015 ; Dreyer et al, 2017 ).…”
Section: Introductionmentioning
confidence: 58%
See 3 more Smart Citations